Effects of a nationwide strategy to reduce salt intake in Samoa - Trieu, K; Ieremia, M; Santos, J; Neal, B; Woodward, M; Moodie, M; Bell, M; Snowdon, W; Faumuina, T; Webster, J (Lippincott, Williams and Wilkins, 2018)
Objective: Salt reduction is one of the most cost-effective interventions for the prevention of noncommunicable diseases, but there are no studies evaluating the effectiveness of national strategies in low or lower middle income countries. This study aimed to examine the effect of an 18-month nation-wide salt reduction strategy in Samoa. Methods: Two nationally representative cross-sectional surveys of adults aged 18–64 years, measuring 24-h urinary salt excretion and salt-related knowledge, attitudes and behaviours, were conducted before (2013) and after (2015) the intervention. Results: There were 234 participants at baseline (response rate 47%) and 479 at 18 months (response rate 61%). There was no change in mean population salt intake between 2013 (7.31 g/day) and 2015 (7.50 g/day) (0.19, 95% confidence interval -0.50 to 0.88; P = 0.588). There were significant changes in the proportion of the population who always or often add discretionary salt when eating (-16.2%, P = 0.002), the proportion who understood the adverse effects of salt (+9.0%, P = 0.049) and the proportion using one or more methods to control their salt intake (+20.9%, P < 0.001). A total of 73% reported that they had heard or seen the salt reduction messages. Conclusion: With widespread awareness of the salt reduction message and some improvements in salt-related knowledge and behaviours following the intervention, Samoa is now well positioned to implement much-needed structural initiatives or policies to reduce salt in the food supply.